2016
DOI: 10.1111/1756-185x.12839
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with Behçet's syndrome: relationship with quality of life, depression, anxiety, disability and disease activity

Abstract: Fatigue is common in clinically active BS patients compared with healthy controls and inactive BS patients. Depression, anxiety and physical dysfunction were significantly associated with fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 30 publications
(35 reference statements)
0
24
1
Order By: Relevance
“…In a Korean study, the proportion of BD patients with depression was 46% . Although Oktayoglu et al detected no significant difference between patients with BD and healthy control subjects in respect of HADS anxiety scores, Ilhan et al showed a significant difference between BD patients and healthy control subjects in HADS anxiety and depression scores, as in the current study . We detected that 40.6% of BD patients had depression and 43.2% had anxiety in this study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In a Korean study, the proportion of BD patients with depression was 46% . Although Oktayoglu et al detected no significant difference between patients with BD and healthy control subjects in respect of HADS anxiety scores, Ilhan et al showed a significant difference between BD patients and healthy control subjects in HADS anxiety and depression scores, as in the current study . We detected that 40.6% of BD patients had depression and 43.2% had anxiety in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…Fatigue can be seen as a symptom of rheumatological and non‐rheumatological diseases . A few recent studies have been conducted about fatigue in BD . BD can affect patients in a negative way and cause fatigue, also reducing quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of major organ involvement can largely be eliminated by immunosuppressive medications in BD, whereas mucocutaneous symptoms, as a mild disease spectrum, can remain active under a mild antiinflammatory agent (frequently colchicine)-based protocol (22)(23)(24)(25). In this context, producing new disease-specific or organspecific outcome measures for use in the decision-making process can be helpful in patient management (22)(23)(24)(25)(26)(27)(28)(29). Productivity loss at work and/or in daily life and diseasespecific fears can be considered as outcome measures in cases of BD; however, there have been no data presented to date regarding this issue.…”
Section: Introductionmentioning
confidence: 99%
“…It has a significant impact on economic life of both employed patients and their employers . On this basis, it is necessary to define work limitation‐related factors in patients with chronic diseases to improve work performance of patients …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] On this basis, it is necessary to define work limitation-related factors in patients with chronic diseases to improve work performance of patients. 2,[6][7][8][9][10][11][12][13][14][15][16] Behçet's syndrome (BS) is a chronic disease presenting as mild disease course regarding mucocutaneous manifestations and musculoskeletal involvement as well as severe disease course with ocular, vascular, central nervous system and gastrointestinal involvement. A severe disease course is commonly seen in males and treated with immunosuppressive medications (IS).…”
Section: Introductionmentioning
confidence: 99%